MO344: Effect of Cancer Stage on Adverse Kidney Outcomes in Patients With Advanced Melanoma Treated With Immune Checkpoint Inhibitors. (3rd May 2022) - Wang, Qiyu; Strohbehn, Ian; Strohbehn, Samuel; Lee, Meghan; Seethapathy, Harish; Hanna, Paul; Fadden, Riley; Reynolds, Kerry; Sullivan, Ryan; Zhao, Sophia; Boland, Genevieve; Sise, Meghan
Abstract: BACKGROUND AND AIMS: Immune checkpoint inhibitor (ICI) therapy has improved the outcome of advanced melanoma but can also lead to kidney injury. Anti-programmed cell death protein 1 (anti-PD-1) therapy is now used in adjuvant setting for stage 3 melanoma after curative intent surgery, and anti-PD-1 or a combination of anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4)/PD-1 therapy is used in stage 4 melanoma. We aimed to compare the incidence and predictors of adverse kidney outcomes in patients with stage 3 and stage 4 melanoma treated with ICIs. METHOD: We conducted a retrospective cohort study including all patients diagnosed with advanced melanoma who initiated ICIs between January 2016 and December 2019 at Mass General Brigham. Acute kidney injury (AKI) was defined as a 1.5-fold rise in creatinine within 1 year of ICI initiation. Sustained AKI was defined as AKI that lasted for > 48 h, and acute interstitial nephritis (AIN) cases (diagnosed by biopsy or clinical criteria) were determined by chart review of all episodes of sustained AKI by two nephrologists. A composite outcome of chronic kidney disease (CKD) was defined by new onset estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m 2 or 30% eGFR decline sustained for 90 days. Non-kidney irAEs were defined by diagnosis codes. Competing risk analysis was used to identify risk factors for adverse kidney outcomes. RESULTS: A total of 855 patients with advanced melanoma were treated with ICIs between 2016 and 2019. The risk of all-cause AKI was 16.6%. Patients with stage 4 melanoma receiving anti-CTLA-4/PD-1 combination therapy had the highest rates of all-cause AKI (27.2%) and AIN (5.7%). Patients with surgically resected stage 3 melanoma treated with adjuvant anti-PD-1 therapy has the lowest absolute risk of all-cause AKI (7.5%); but the aetiology of AKI was enriched for AIN in stage 3 melanoma (causing 62.5% of all cases of AKI sustained >48 h) (Fig. 1 ). In the multivariable Fine-Gray model, cancer stage and ICI treatment regimen were the top predictors of AKI. Patients with stage 4 melanoma treated with anti-PD-1 monotherapy were more than two times likely to develop AKI within the first year compared with patients with stage 3 melanoma [aHR 2.18, 95% confidence interval (95% CI) 1.29–3.74; P < .01), while patients with stage 4 melanoma treated with anti-CTLA-4/PD-1 combination therapy were more than four times likely to develop AKI (aHR 4.36, 95% CI 2.58–7.39; P < .01) compared with patients with stage 3 melanoma (Fig. 2 ). Baseline CKD, diabetes, hypertension, cirrhosis and proton pump inhibitor use were not significantly associated with the risk of developing AKI. For AIN, only anti-CTLA-4/PD-1 combination therapy use was significantly associated with the outcome (aHR 4.17, 95% CI 1.28–13.54; P = .02). There was no increase in the risk of AIN in patients with stage 4 melanoma receiving anti-PD-1 monotherapy compared with stage 3 melanoma (Fig. 2 ). Among patients surviving > 4 years, 20% developed the composite CKD outcome. We identified a similar trend across the three cohorts for kidney and non-kidney irAEs: patients with stage 3 and stage 4 melanoma treated with anti-PD-1 monotherapy had similar rates of non-kidney irAEs (60% in stage 3 versus 52.7% in stage 4, P = .2), while patients with stage 4 melanoma treated with anti-CTLA-4/PD-1 combination therapy experienced higher rates of non-kidney irAEs (72%, P = .01). CONCLUSION: Anti-CTLA-4/PD-1 combination therapy is associated with a higher risk of all-cause AKI and AIN. Incidence of AIN is similar between patients with stage 3 and stage 4 melanoma receiving anti-PD-1 monotherapy. Among patients with stage 3 melanoma, AKI aetiology is enriched for AIN. Survivors are at high risk of CKD regardless of cancer stage.